Tool Life Analysis Of The Car Leaf Spring - Fusito HY (Universitas Sriwijaya, 2016)
Car leaf spring NISSAN CK12 included in the class of spring steel. The main properties of the steel spring are the elastic modulus and elastic limit. This study aimed to analyze the age and tool wear made from the leaf spring NISSAN CK12 and the HSS. This study uses a conventional lathe tool and Electronic Microscope to take a micro image of the eyes of the tool. The average value of hardness is highest in lathe tool from the leaf spring NISSAN CK12 which treated by Quenching 800ÂºC holding time of 60 minutes (heat treatment) hardness value by an average of 638.082 HV and from HSS lathe tool amounted to 623.723 HV. From the results obtained on the lathe Tool HSS during the cutting speed Vc = 66.7 m / min VB = 0.3017 tc = 7.17 min f = 0.3 mm / put, Non Treatment tool during the cutting speed Vc = 66 , 7 m / min, a = 0.7 mm VB = 0.3061 with tc = 6.77 minutes. Heat Treatment tool on cutting speed Vc = 66.7 m / min f = 0.3 m / put a = 0.7 mm VB = 0.3051 tc = 6.77 minutes. From the test results it can be concluded that the cutting speed (Vc) 66.7 m / min with a depth of 0.7 mm eating the entire tool wear results can be seen in cutting speed (Vc) 66.7 m / min with a depth of 0.7 mm that the tool of the leaf spring car given the heat treatment has a longer lifespan tools age compared with the leaf spring car Non Treatment. While the HSS has age and the wear rate which is higher than the second tool of the leaf spring car. As seen in HSS tool, the tool age is 1,41 min, Heat treatment tool 1,45 min, non heat treatment tool 1,46 min.